Early Earth mantle heterogeneity revealed by light oxygen isotopes of Archaean komatiites - Byerly, Benjamin L.; Kareem, Keena; Bao, Huiming; Byerly, Gary R. (Nature geoscience, 2017)
Geodynamic processes on early Earth, especially the interaction between the crust and deep mantle, are poorly constrained and subject to much debate. The rarity of fresh igneous materials more than 3 billion years old accounts for much of this uncertainty. Here we examine 3.27-billion-year-old komatiite lavas from Weltevreden Formation in the Barberton greenstone belt, which is part of the Kaapvaal Craton in Southern Africa. We show that primary magmatic compositions of olivine are well preserved in these lavas based on major and trace element systematics. These komatiitic lavas represent products of deep mantle plumes. Oxygen isotope compositions (δ 18 O) of the fresh olivine measured by laser fluorination are consistently lighter (about 2‰) than those obtained from modern mantle-derived volcanic rocks. These results suggest a mantle source for the Weltevreden komatiites that is unlike the modern mantle and one that reflects mantle heterogeneity left over from a Hadean magma ocean. The anomalously light δ 18 O may have resulted from fractionation of deep magma ocean phases, as has been proposed to explain lithophile and siderophile isotope compositions of Archaean komatiites. Lavas sourced from Archaean mantle plumes have anomalously light oxygen isotope signatures, according to geochemical analyses of lava samples from southern Africa. The results imply that Earth’s early mantle was heterogeneous.